PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KARYAWAN SEBAGAI VARIABEL INTERVENING PADA PT BANK NEGARA INDONESIA CABANG BATAM - Heryenzus heryenzus; Restui Laia (Universitas Putera Batam, 2018)
This study aims to determine the effect of compensation, motivation, compensation on employee performance, employee performance motivation and to determine the effect of job satisfaction on employee performance at PT. Bank Negara Indonesi Batam Branch. This study uses saturated samples for all employees at PT. Bank Negara Indonesi Batam Branch. Analysis method of this research using path analysis. Based on the results of the analysis found that compensation has a positive effect on job satisfaction, motivation has a positive and significant effect on job satisfaction, compensation has a positive and significant impact on employee performance, motivation has a positive and significant impact on employee performance, job satisfaction has a positive and significant influence on performance and employee satisfaction. Working mediates the effect of compensation and motivation on employee performance. Based on research results, PT. Bank Negara Indonesi Batam Branch. Should be fair compensation, motivate employees with promotion.